Transcutaneous Spinal Cord Direct-Current Stimulation Modulates Functional Activity and Integration in Idiopathic Restless Legs Syndrome - Zeng, Min; Wang, Li; Cheng, Bochao; Qi, Guiqiang; He, Junwei; Xu, Zhexue; Han, Tao; Liu, Chunyan; Wang, Yuping (Frontiers in Neuroscience, 2020)
Idiopathic restless legs syndrome (RLS) is a sensorimotor disorder and is suggested to be caused by central nervous system abnormalities. Non-invasive transcutaneous spinal direct current stimulation (tsDCS) was recently used for RLS therapy. However, the neurophysiological basis of tsDCS treatment is still unknown. In this study, we explored the neural basis of tsDCS in 15 RLS patients and 20 gender- and age-matched healthy controls using resting-state functional magnetic resonance imaging (rs-fMRI). We calculated the whole-brain voxel-wise fractional amplitude of low frequency fluctuations (fALFF), regional homogeneity (ReHo), and weighted degree centrality (DC) to characterize the intrinsic functional activities, local and global functional integration. We found that tsDCS can effectively improve the sleep and RLS symptoms in RLS patients. Moreover, after tsDCS therapy, RLS patients showed decreased fALFF in right anterior insula/temporal pole, decreased ReHo in supplementary motor area, increased weighted DC in left primary visual cortex and decreased weighted DC in right posterior cerebellum. The changed patterns were consistent with that found between RLS patients and healthy controls. The weighted DC in left primary visual cortex after treatment and the fALFF in right anterior insula/temporal pole before treatment were significantly and marginally correlated with sleep and RLS symptom scores, respectively. These results revealed that tsDCS can normalize the functional patterns of the RLS patients and is an effective way for RLS therapy. Our findings provide the neurophysiological basis for tsDCS treatment and may facilitate understanding the neuropathology of RLS and directing other neuromodulation treatments.